Asking the audience : participatory art in 1980s New York - Rounthwaite, Adair (University of Minnesota Press, 2017)
Introduction: recovering audience -- The politics of participation -- The pedagogical subject of participation -- Photography, agency, and participation -- Art, affect, crisis -- Conclusion: partcipation in the present.